The Schistosoma mansoni Cytochrome P450 (CYP3050A1) Is Essential for Worm Survival and Egg Development. - Peter D Ziniel; Bhargava Karumudi; Andrew H Barnard; Ethan M S Fisher; Gregory R J Thatcher; Larissa M Podust; David L Williams (Public Library of Science (PLoS), 2015)
Schistosomiasis affects millions of people in developing countries and is responsible for more than 200,000 deaths annually. Because of toxicity and limited spectrum of activity of alternatives, there is effectively only one drug, praziquantel, available for its treatment. Recent data suggest that drug resistance could soon be a problem. There is therefore the need to identify new drug targets and develop drugs for the treatment of schistosomiasis. Analysis of the Schistosoma mansoni genome sequence for proteins involved in detoxification processes found that it encodes a single cytochrome P450 (CYP450) gene. Here we report that the 1452 bp open reading frame has a characteristic heme-binding region in its catalytic domain with a conserved heme ligating cysteine, a hydrophobic leader sequence present as the membrane interacting region, and overall structural conservation. The highest sequence identity to human CYP450s is 22%. Double stranded RNA (dsRNA) silencing of S. mansoni (Sm)CYP450 in schistosomula results in worm death. Treating larval or adult worms with antifungal azole CYP450 inhibitors results in worm death at low micromolar concentrations. In addition, combinations of SmCYP450-specific dsRNA and miconazole show additive schistosomicidal effects supporting the hypothesis that SmCYP450 is the target of miconazole. Treatment of developing S. mansoni eggs with miconazole results in a dose dependent arrest in embryonic development. Our results indicate that SmCYP450 is essential for worm survival and egg development and validates it as a novel drug target. Preliminary structure-activity relationship suggests that the 1-(2,4-dichlorophenyl)-2-(1H-imidazol-1-yl)ethan-1-ol moiety of miconazole is necessary for activity and that miconazole activity and selectivity could be improved by rational drug design.